2021
DOI: 10.1177/1077801221992872
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Intimate Partner Violence and Associated Factors Among HIV-Infected Women in Rural South Africa: A Longitudinal Study

Abstract: Intimate partner violence (IPV) has been highlighted as one of the challenges to the effectiveness of the Prevention of Mother-to-Child Transmission of HIV (PMTCT) programs in rural areas in South Africa. This study aimed at assessing the prevalence of prenatal and postnatal physical as well as psychological IPV, and corresponding time-invariant and time-varying predictors, among HIV-positive women attending PMTCT services in rural South Africa. The Conflict Tactics Scale (CTS) was used to assess IPV at four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…11 , 16 In SSA, IPV prevalence ranges from 20% to 60% among pregnant/postpartum women living with HIV. 17 20 Considering global ambitions to eliminate vertical HIV transmissions by 2030, 21 the high rates of both prevalent and incident IPV among pregnant women living with HIV are particularly concerning. This is because pregnant women living with HIV reporting IPV are more likely not to adhere to ART thereby leading to unsuppressed viral load and subsequent elevated risk of vertical transmission.…”
Section: Introductionmentioning
confidence: 99%
“…11 , 16 In SSA, IPV prevalence ranges from 20% to 60% among pregnant/postpartum women living with HIV. 17 20 Considering global ambitions to eliminate vertical HIV transmissions by 2030, 21 the high rates of both prevalent and incident IPV among pregnant women living with HIV are particularly concerning. This is because pregnant women living with HIV reporting IPV are more likely not to adhere to ART thereby leading to unsuppressed viral load and subsequent elevated risk of vertical transmission.…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 scoping review improved representation from African clinical samples and found that WLH who experienced VAW (as defined by the primary articles included in the review, including intimate partner violence or violence regardless of the perpetrator) were less likely to engage in HIV care and treatment, including ART uptake and adherence [ 14 ]. Clinical samples have confirmed these associations in African settings [ 15 , 16 , 17 ] but these are methodologically limited as participants are often actively engaged in healthcare.…”
Section: Introductionmentioning
confidence: 99%